2021
DOI: 10.3390/pharmaceutics13060871
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of PEGylated Starch-Coated Iron Oxide Nanoparticles for Enhanced Photothermal Cancer Therapy

Abstract: Iron oxide nanoparticles (IONPs) possess versatile utility in cancer theranostics, thus, they have drawn enormous interest in the cancer research field. Herein, we prepared polyethylene glycol (PEG)-conjugated and starch-coated IONPs (“PEG–starch–IONPs”), and assessed their applicability for photothermal treatment (PTT) of cancer. The prepared PEG–starch–IONPs were investigated for their physical properties by transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…For example, polyethylene glycol (PEG)-conjugated and starch-coated MNPs (PEG–starch–MNPs) for enhanced photothermal cancer therapy (PTT) were developed. The authors found that plasma half-life of PEG–starch–MNPs was 2.7 h, whereas, to compare, t 1/2 of starch–MNPs was 5.8 min [ 84 ].…”
Section: Intravenously Injected Mnpsmentioning
confidence: 99%
“…For example, polyethylene glycol (PEG)-conjugated and starch-coated MNPs (PEG–starch–MNPs) for enhanced photothermal cancer therapy (PTT) were developed. The authors found that plasma half-life of PEG–starch–MNPs was 2.7 h, whereas, to compare, t 1/2 of starch–MNPs was 5.8 min [ 84 ].…”
Section: Intravenously Injected Mnpsmentioning
confidence: 99%
“…According to Cretu and coauthors (2021), as IONPs have a high area/volume ratio, magnetization, Van der Waals forces and high surface energy, they tend to aggregate (Crețu et al, 2021). Therefore, these nanoparticles can have their surface stabilized, coated and/or functionalized, which provides greater applicability (Amatya et al, 2021;Crețu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As the behavior of IONPs in the biomedical field is influenced by three variables, including morphology, size and surface characteristics, experimental parameters such as the presence of surfactants, Fe 2+ /Fe 3+ ratio, salt type, pH control, electrical force, nature of the alkaline agent (NaOH, Na2CO3, NH4OH), stirring rate, nitrogen or argon flow in the system, and temperature or time of reaction are some of the factors that can affect the physical characteristics of nanoparticles and influence their biological properties, as the rate of blood circulation, cellular absorption, and biodistribution (Hernández-Hernández et al, 2020;Crețu et al, 2021;Amatya et al, 2021). The shape, size, crystal structure, chemical composition, and dispersibility of nanoparticles directly affects their physical and chemical properties, and consequently also the performance of such materials in a bunch of applications (Shabatina et al, 2020;Ajinkya et al, 2020;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Amatya et al studied the photothermal activity of iron oxide nanoparticles modified with PEG and starch to prevent aggregation and improve biocompatibility [160]. The modified nanoparticles were employed as PTT agents to treat cancer under an 885 nm NIR I laser.…”
Section: Exposure Limits Correction Factor Cmentioning
confidence: 99%